Student anti-war demonstration - Spartan Daily, Koski:::Creator::::::::::::
Student anti-war protest at San Jose State College. This view depicts a student leaving the field where the ROTC are gathered in formation. An administrator and campus police officer are present behind the student. The students opposed the presence of the ROTC on campus.